Fazendo a pele no auto do círio: processos criativos da maquiagem da comissão de frente - VASCONCELOS, Iam Nascimento (Universidade Federal do Pará, 2019)
This research seeks to understand as creative artist-researcher-participant of Auto do Círio the creative processes of makeup of the Front Commission revealed in the spectacularity of this scenic phenomenon of singular dimensions as dramatic courtship. Armindo Bião (2008), Jean-Marie Pradier (1995) for the approach to Spectacularity, Theatricality, Cultural Matrices - Aesthetic Matrices, and Theoretical and Methodological Matrices in Ethnocenology, as Ethnoscience of Arts and Forms of Spectacle. Michel Maffesoli for Emotional Communities. In the study of the imaginary Paes Loureiro (2010) in his proposition of Semiotic Conversion as a conceptual key to understanding the poetics of Amazonian culture. For the Creative Processes approach, Sônia Rangel (2015) and Philip Hallawell (2010). As a dominant ethnocenological premise, we privilege in the methodological procedures the multiple internal experiences in the research phenomenon, giving relevance to the wisdom of practitioners and their trajectories in the show, through photographic records, videos of the creative process of self makeup and choreography, as well as semi interviews structured. These audiovisual records compose a documentary titled Auto Etnodocumentario indissociated from this reflection contributing, as a makeup artist, to the construction of knowledge that springs from the complexity and richness of spectacular street practices in the contemporary Amazon